Morphological development of the neopallium during the prenatal stage in alpaca (Vicugna pacos) - Roldán M., Susana (2022)
The aim of this study was to describe the macroscopic anatomy of the neopallium in alpaca foetuses. Fifteen foetuses with gestational ages ranging from days 101 to 323 were used. The brains were infiltrated with 10% formaldehyde by injections at the frontoparietal and nasofrontal junction of the skull. Then, 30 days later the brains were dissected and the neopallium was exposed. Photographs in situ and ex situ of the dorsal, lateral, rostral, caudal, and ventral view were taken. By using the pictures, the brain sulcus and gyri were identified. In chronological order, the sulcus that were described were: Lateral Fissure, Suprasylvian Sulcus, Endosagittal Sulcus, Coronal Sulcus, Splenial Sulcus, Genual Sulcus, Calcarine Sulcus, Presylvian Sulcus, Central Sulcus, Sagittal Sulcus, Ectosagittal Sulcus, Diagonal Sulcus and Ectosilvian Sulcus. The gyrus were: Cingulate Gyrus, Rostral Silvian Gyrus, Caudal Silvian Gyrus, Sagittal Gyrus, Postcentral Gyrus, Precentral Gyrus, Middle Ectosylvian Gyrus, Caudal Ectosylvian Gyrus and Middle Ectosagittal Gyrus. An asymmetry between hemispheres of the same individual was evidenced, both due to the length and shape of some sulcus and gyrus, as well as their location.